Pengaruh Suhu Terhadap Siklus Hidup Lalat Buah (Drosophila melanogaster) - Suharsono, Suharsono; Nuryadin, Egi (Universitas Muhammadiyah Surakarta, 2019)
Fruit flies (Drosophila melanogaster) generally have four phases in their life cycle, namely eggs, larvae, pupae and imago. In general, Drosophila melanogaster experiences a life cycle of 8-11 days at optimal temperatures. At lower temperatures the time required to complete its life cycle is relatively longer and slower which is around 18-20 days. Whereas at higher temperatures adult flies that grow will be sterile. The development period of Drosophila melanogaster in its life cycle is influenced by several factors, namely ambient temperature, food availability, level of maintenance density and light intensity. This study aims to determine the effect of temperature on the life cycle of fruit flies (Drosophila melanogaster). The study will be analyzed using quantitative analysis using randomized block design (RBD) with six temperature difference treatments for each treatment and repeated 4 times so that there are 24 experiments. The results showed the development in the Drosophila melanogaster cycle starting from Egg - Larva (Instar I) - Larva (Instar II) - Larva (Instar III) - Pre Pupa - Pupa - Imago. The life cycle of Drosophila melanogaster has an average of 42.08 hours or 1.75 days up to 79.96 hours or 3.33 days in each treatment. And obtained a fast time during the life cycle of Drosophila melanogaster at a temperature of 30°C is 10.47 days and the longest at a temperature of 18°C is 18.35 days.